Prenatal diagnosis and molecular cytogenetic characterization of a 1.07-Mb microdeletion at 5q35.2-q35.3 associated with NSD1 haploinsufficiency and Sotos syndrome - Chih-Ping Chen; Chen-Ju Lin; Schu-Rern Chern; Yu-Peng Liu; Yu-Ling Kuo; Yen-Ni Chen; Peih-Shan Wu; Dai-Dyi Town; Li-Feng Chen; Chien-Wen Yang; Wayseen Wang (Elsevier, 2014)
Objective: To present prenatal diagnosis and molecular cytogenetic characterization of a de novo 5q35 microdeletion associated with Sotos syndrome. Methods: This was the first pregnancy of a 29-year-old woman. The pregnancy was uneventful until 27 weeks of gestation when left ventriculomegaly was first noted. At 31 weeks of gestation, polyhydramnios, macrocephaly, and ventriculomegaly were prominent on ultrasound, and left pyelectasis and bilateral ventriculomegaly were diagnosed on magnetic resonance imaging. The woman underwent amniocentesis and cordocentesis at 32 weeks of gestation. Conventional cytogenetic analysis was performed using cultured amniocytes and cord blood lymphocytes. Array comparative genomic hybridization (aCGH) was performed on uncultured amniocytes and parental blood. Metaphase fluorescence in situ hybridization (FISH) was performed on cultured lymphocytes. Results: Conventional cytogenetics revealed a karyotype of 46,XX. aCGH on uncultured amniocytes revealed a de novo 1.07-Mb microdeletion at 5q35.2-q35.3 encompassing NSD1. Metaphase FISH analysis on the cord blood lymphocytes confirmed the deletion at 5q35.2. The postnatal phenotype was consistent with Sotos syndrome. Conclusion: Fetuses with Sotos syndrome may present macrocephaly, polyhydramnios, ventriculomegaly, and pyelectasis in the third trimester. aCGH and metaphase FISH are useful for rapid diagnosis of 5q35 microdeletion associated with Sotos syndrome.